Delays in Treatment-Seeking Decisions Among Women With Myocardial Infarction. Issue 5 (September 2017) - Arslanian-Engoren, Cynthia; Scott, Linda D.
Abstract : Background: Minimizing the time from myocardial infarction (MI) symptom onset to the implementation of lifesaving interventions decreases morbidity and mortality of women who experience an MI. However, not all women seek timely evaluation and treatment for their MI symptoms. Objectives: The aim of this article is to describe reasons for decision treatment delays among women who experience an initial MI. Method: A secondary analysis of narrative data collected as part of a qualitative study examining the triage experiences of women (N = 14) who presented to the emergency department with symptoms of acute MI. The data were analyzed using the Krueger method. Results: Women with severe symptoms sought immediate evaluation. However, 9 of the 14 participants reported delays in seeking immediate evaluation and treatment for MI. Four of the participants who delayed were health care professionals (3 nurses, 1 respiratory therapist). Content analysis revealed 3 themes accounting for the delay: lack of association of symptoms with MI, personal/professional obligations, and refusal to arrive via ambulance. Discussion: Some women who experience MI continue to delay despite symptoms of nausea, indigestion, and fatigue as well as a family history of heart disease and recommendations to the contrary. Reducing delays will improve survival and minimize morbidity and mortality for women who suffer an acute MI.